Man’s Journey Through Space, Time and Logos. Reflections of Narcissus’ Myth in Solarium by Jordan Zandi - Claudia Pisoschi (European Scientific Journal, ESJ, 2018)
The paper is meant to be a text analysis of the poem Solarium by Jordan Zandi in point of the significance of space, time and logos dimensions. The pragma-stylistic perspective adopted will allow us to identify how Narcissus’ myth is reflected in Zandi’s poem by comparing it to the complex reference text which is Ovid’s Metamorphoses (Book III). Like Narcissus, the poetic voice in Solarium makes a journey through time and space. Primordial elements (fire, air, water, earth) with their infinite concrete manifestations are symbols of the continuous change chain that life and death are part of. Man himself becomes not only the (gradually aware) subject, but also the symbolic expression, of a total metamorphosis of matter into conscience through logos.